Spreading the VISIR remote lab along Argentina. The experience in Patagonia - Hernández-Jayo, Unai (2017)
The learning of technical and science disciplines requires experimental and practical training. Hands-on labs are the natural scenarios where practical skills can be developed but, thanks to Information and Communication Technologies (ICT), virtual and remote labs can provide a framework where Science, Technology, Engineering and Mathematics (STEM) disciplines can also be developed. One of these remote labs is the Virtual Instruments System in Reality (VISIR), specially designed to practice in the area of analog electronics. This paper aims at describing how this remote lab is being used in the Universidad Nacional de la Patagonia San Juan Bosco (UNPSJB - Argentina), in the framework of the VISIR+ project funded by the Erasmus+ Program, one institution without previous experiences with remote labs.